Pemanfaatan AI dalam Proses Editing Video Promosi pada Akun Instagram Rama Dauhan Design Studio - Kamal, Raden Rubensyach Nalendra; Riyanto, Sutisna (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
Communication plays a crucial role in human life, especially in building social interactions and conveying information. The development of digital technology has brought significant changes, particularly in the business world, which relies on social media as an effective promotional tool. Instagram has become a primary platform for distributing engaging promotional content and building brand image. Video editing is a critical stage in creating promotional content, where artificial intelligence (AI) technology is increasingly utilized to improve efficiency and the quality of the final output. This final project aims to identify the elements of video editing and AI used, as well as describe the promotional video editing process at Rama Dauhan Design Studio. The Agile development method is applied to support an adaptive and iterative production process. The results of this project are expected to provide insights into strategies for utilizing AI in promotional video editing and its contribution to strengthening promotion and the visual appeal of products. This project serves as an important reference for developing promotional video production based on advancing digital technology.